2019
DOI: 10.1371/journal.pone.0210509
|View full text |Cite
|
Sign up to set email alerts
|

Health complaints among adolescents in Norway: A twenty-year perspective on trends

Abstract: PurposeExamine time trends in health complaints among adolescents in Norway between 1994 and 2014 and among population subgroups, e.g., age and gender, as well as their interactions.MethodsNorwegian data on 11-16-year-olds were drawn from the Health Behaviour in School-aged Children survey (HBSC) and analyzed for 1994 (n = 4,952), 1998 (n = 5,026), 2002 (n = 5,023), 2006 (n = 4,711), 2010 (n = 4,342) and 2014 (n = 3,422). Design adjusted linear regression that accounts for clustering effects was used to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
76
5
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(113 citation statements)
references
References 38 publications
(53 reference statements)
16
76
5
6
Order By: Relevance
“…These results do not follow previous ndings which indicated that the decline in mental well-being is slightly stronger for older adolescents compared to younger ones [5,11]. In Norway, an increasing trend in health complaints among adolescents from 1994 to 2014 was found, especially among older adolescent girls [11]. In Sweden the increase over time in psychological complaints (1985 to 2005) was seen in older adolescents (boys and girls), whereas no signi cant change was seen in the youngest groups (11-year olds) [14].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results do not follow previous ndings which indicated that the decline in mental well-being is slightly stronger for older adolescents compared to younger ones [5,11]. In Norway, an increasing trend in health complaints among adolescents from 1994 to 2014 was found, especially among older adolescent girls [11]. In Sweden the increase over time in psychological complaints (1985 to 2005) was seen in older adolescents (boys and girls), whereas no signi cant change was seen in the youngest groups (11-year olds) [14].…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, previous research argued that interaction of mental health outcomes and sociodemographic characteristics as gender, age and socio-economic status showed a large cross-national variability (e.g., [36]), which may explain why the changes in associations over time were less emphasized in Czechia. These results do not follow previous ndings which indicated that the decline in mental well-being is slightly stronger for older adolescents compared to younger ones [5,11]. In Norway, an increasing trend in health complaints among adolescents from 1994 to 2014 was found, especially among older adolescent girls [11].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…among 15-year-olds rose from 21.8 % to 32.5% from 1994 to 2010. 220 The rise in health complaints appears to be more evident among older adolescent girls, 224 who also in general tend to report higher levels of health complaints than boys. [225][226][227][228] Health complaints have been linked to negative outcomes such as school absence and lower educational attainment among youth and young adults, 229,230 and to be a strong predictor of work absenteeism in adults.…”
Section: Health Complaints In Adolescencementioning
confidence: 99%
“…Health of coming generations still tends to deteriorate and requires immediate attention given to it by the overall society [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%